Separation of cobalt and nickel from chloride leach solution of nickel laterite ore by solvent extraction. Issue 5 (2nd September 2016) - Liu, Yang; Lee, Man Seung
Abstract: In order to separate Ni and Co from the chloride leach solution of laterite ores with high Fe content, solvent extraction and stripping experiments were performed. Various extractants, such as cationic extractants (Cyanex 272 (di(2, 4, 4-trimethylpentyl)phosphinic acid)), D2EHPA (di-2-ethylhexyl phosphoric acid), Versatic 10 (a carboxylic acid), amine extractants (Alamine 336 (tri-octyl/dodecyl amine), Aliquat 336 (a mixture of tri-octyl/decyl ammonium chloride), etc.), and neutral extractant (TBP (tri-butyl phosphate)) have been tested. Most of the Co together with some amount of Fe and Mn was extracted by Aliquat 336. The purified Co solution was obtained by extraction with Cyanex 301 (dialky1dithiophosphinic acid) after stripping the loaded Aliquat 336. Extraction of the filtrate with saponified Versatic 10 after precipitation of Al resulted in the separation of Ni and Mn from Ca and Mg. Ni was then selectively stripped by H2 SO4 solution. The nickel solution with 99% purity was obtained from the batch simulation experiments.